Stockholm score of lesion detection on computed tomography following mild traumatic brain injury (SELECT-TBI): study protocol for a multicentre, retrospective, observational cohort study. Issue 9 (1st September 2022) - Fletcher‑Sandersjöö, Alexander; Tatter, Charles; Yang, Li; Pontén, Emeli; Boman, Magnus; Lassarén, Philipp; Forsberg, Sune; Grönlund, Ingrid; Tidehag, Viktor; Rubenson-Wahlin, Rebecka; Strömmer, Lovisa; Westberg, Karin; et al.
Abstract : Introduction: Mild traumatic brain injury (mTBI) is one of the most common reasons for emergency department (ED) visits. A portion of patients with mTBI will develop an intracranial lesion that might require medical or surgical intervention. In these patients, swift diagnosis and management is paramount. Several guidelines have been developed to help direct patients with mTBI for head CT scanning, but they lack specificity, do not consider the interactions between risk factors and do not provide an individualised estimate of intracranial lesion risk. The aim of this study is to create a model that estimates individualised intracranial lesion risks in patients with mTBI who present to the ED. Methods and analysis: This will be a retrospective cohort study conducted at ED hospitals in Stockholm, Sweden. Eligible patients are adults (≥15 years) with mTBI who presented to the ED within 24 hours of injury and performed a CT scan. The primary outcome will be a traumatic lesion on head CT. The secondary outcomes will be any clinically significant lesion, defined as an intracranial finding that led to neurosurgical intervention, hospital admission ≥48 hours due to TBI or death due to TBI. Machine-learning models will be applied to create scores predicting the primary and secondary outcomes. An estimated 20 000 patients will be included. Ethics and dissemination: The study has been approved by the Swedish Ethical Review Authority (Dnr: 2020-05728). The research findings will be disseminated through peer-reviewed scientific publications and presentations at international conferences. Trial registration number: NCT04995068 .